Hepatic histological comparison between Acute Self-limiting Hepatitis A and Hepatitis E - Kazuyuki Suzuki; Yoshitoku Tatemichi; Yuichi Yoshida; Yasuhiro Miyamoto; Hidekatsu Kuroda; Akio Miyasaka; Yasuhiro Takikawa; Tomoyuki Masuda; Ichiro Kumagai; Hiroaki Okamoto (Archives of Hepatitis Research - Peertechz Publications, 2017)
Background: Histological fi ndings of the liver in acute liver injury are basically affected by degree of liver damage. However, the differences in liver histology between acute self-limiting hepatitis A (AH-A) and hepatitis E (AH-E) have not yet been clarifi ed. This study aimed to clarify the differences in histological fi ndings of the liver between AH-A and AH-E. Methods: Fourteen patients with AH-A and 11 patients with AH-E matched with the period between the onset of AH and the performance of liver biopsy and with the degree of liver function impairment were studied. The activity grade and fi brosis stage were evaluated using the METAVIR scoring system and the semiquantitative scores using 9 items from histological fi ndings: interface hepatitis, portal lymphocytes, portal neutrophils, lobular necrosis, lobular infl ammation, steatosis, ballooning, Mallory bodies, and cholestasis. Results: The patients with AH-E were signifi cantly older and had a higher proportion of males than the patients with AH-A. Although liver function test values and prothrombin time on admission signifi cantly differed between AH-A and AH-E, these values on the day of liver biopsy were not signifi cantly different between AH-A and AH-E. Among the histological scores studied, lobular necrosis score was signifi cantly higher in AH-A than in AH-E. Alcohol abuse did not affect the histological differences between AH-A and AH-E. Among the AH-E patients, activity grade, lobular necrosis, and lobular infl ammation scores were signifi cantly high in patients showing positive drug-induced lymphocyte stimulation tests. Conclusions: The lobular necrosis score among the histological fi ndings of the liver was signifi cantly higher in AH-A than in AH-E. Aging and immunoreaction against drugs might contribute to the histological changes in AH-E.